PENINGKATAN KEMAMPUAN BAHASA INGGRIS IBU DAN ANAK DENGAN MENGGUNAKAN METODE TPR KELOMPOK PKK VILLA MUKA KUNING - Yessie Aldriani; Melly Siska Suryani (PUAN INDONESIA, 2020)
There are some methods used in teaching English. One of them is TPR (Total Physical Response). This method was used for mothers and children in Villa Muka Kuning because it doesn’t only concern on language skill but it will make participants actively engange in learning process. In this community services, TPR method was applied by using flash cards, songs and games. After conducting the community services, it showed that both mothers and childres were very excited learning English. Moreover, the ability of mothers in teaching English to their children ran more effectively. It is hoped that mothers can optimize their ability in learning English. Therefore, they can teach their children learning English